Indian constitution and the protection of women - Begum, Syed Mehartaj (2012)
Women constitute nearly half of the population, but their status in the society is miserable. Though government is working towards the betterment and upliftment of women, their condition is still miserable. This requires a considerable revisit of governmental policies and programmes. The focus must be target oriented, especially for the rural women, and there is need to ensure that the fruits of the governmental schemes and programmes reach them. Constitutional and legal provisions and policies need to be publicised extensively, especially in the rural and remote areas. - Reproduced.
Keywords: Women - India; India. Constitution; Constitutions